The Impact of Islamic Financial Inspection Thought on the Development of Inspection and comparing it with Positive Thought: Theoretical Comparative Study (Journal of Accounting and Financial Studies ( JAFS ), 2012)
You Mohammed, you're prophet of God and I'm Gabriel)). With this heavenly call which Mohammed, the messenger of God (may God's mercies be on him), got and when he left Hiraa cave and after getting the aye ((read with your God's name)), a new period of mankind's history started. From that time, the greatest state was established. There was no public treasury and no public financial resources at that time. Abu Baker (God bless him) spent a lot of money to support the costs of the new mission. After Al-Hijra, the bases of establishing the Islamic state were available but it lacked administrative and financial organizing. Therefore the prophet was very keen to find Islamic system which ensures justice and availability of foundations of establishing pillars of the Islamic state. The Islamic Sharia has set the rules of financial inspection and it has had dawawin which implemented financial effective control on state’s funds and protecting it against tampering and loss. In addition, there was self-control due to the deep Islamic faith. In spite of the many differences between Islamic financial and administrative systems and the modern states at that time, but the use of dawawin for example bait al-mal, crisis diwan, correspondence and reviews diwan, al- muhtasib diwan in addition to internal control systems tightened the control on bait al-mal resources. Each one has its important role in achieving balance between the incomes and outcomes with the aim at protecting the public fund from theft and tampering. That the imposition of Islamic financial control procedures at all stages of the collection of revenues and spending to reach the target, verify and impose tight control on the performance of employees and the procedures followed and controls are still applied in modern control systems.